Strategi Mempertahankan Usaha Franchise Pada Minuman Mixue di Indonesia - Najla Najla; Yani Dewanthi; Erwin Permana (Universitas Veteran Bangun Nusantara, 2022)
The franchise system provides various advantages for people who buy the system. By using a franchise system, it can provide benefits such as a business brand, logo, marketing, production methods, brand name, and a business system that has also been built from the start. One of the products that runs the franchise strategy to develop its business is the Mixue product. Even though it is relatively new, Mixue has experienced extraordinary development with quite high popularity. This study aims to analyze the strategy of maintaining a franchise business on Mixue drinks in Indonesia. The research was conducted with a qualitative approach. The collection technique uses searches on various official and popular sites as well as reviews of various official publications and scientific publications on the results of scientific research. The results of the study show that Mixue uses three strategies to maintain its business, namely producing contemporary products, low price strategy and FOMO strategy. With these three strategies, Mixue is competent enough to be able to maintain the franchise business. In Indonesia, they also have many outlets and can keep mixue popular among ice cream or boba drink products. Mixue is also able to compete with other companies that offer similar products at higher prices. The mixue outlet consistently applies the franchise concept as a mainstay for developing a business with very positive results. The researcher suggests Mixue business actors to develop new strategies in addition to maintaining existing strategies. The new strategy suggested is for example, business collaboration with complementary products that are well known in Indonesia, for example culinary shops that do not yet serve similar drinks, such as waroeng Special Sambal, solaria fried rice, etc. It is suggested to further researchers to conduct an analysis on the digital marketing aspects of Mixue products.